2016
DOI: 10.1097/nne.0000000000000201
|View full text |Cite
|
Sign up to set email alerts
|

Student Perception of Improvement in Communication and Value in 2 Interprofessional Education Delivery Formats

Abstract: A preferred format to deliver interprofessional education (IPE) has not been described. The aim of this study was to compare students' (N = 150) perceived value and improvement in communication between an IPE activity delivered using a comprehensive versus an abbreviated format. Although both formats were perceived by students to improve their communication skills and add value to their education, students indicated the abbreviated format was more effective than the comprehensive format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…The World Health Organization (WHO), the Institute of Medicine (IOM), and the Interprofessional Education Collaborative (IPEC) all identify IPE as crucial for the practice of health care professionals and as necessary to improve the quality of health care in the United States (IEPC, 2016; IOM, 2011; WHO, 2016). Evidence demonstrates that poor collaboration and communication between health care professionals contributes to communication errors negatively affecting patient safety and the quality of care (Arentsen et al, 2016; Cranford & Bates, 2015; Kahaleh, Danielson, Franson, Nuffer, & Umland, 2015). As a result, nursing educators are now required to include IPE content in their curricula (Poirier, & Wilhelm, 2013).…”
Section: Interprofessional Education and The Role Of Chaplaincy In Hementioning
confidence: 99%
“…The World Health Organization (WHO), the Institute of Medicine (IOM), and the Interprofessional Education Collaborative (IPEC) all identify IPE as crucial for the practice of health care professionals and as necessary to improve the quality of health care in the United States (IEPC, 2016; IOM, 2011; WHO, 2016). Evidence demonstrates that poor collaboration and communication between health care professionals contributes to communication errors negatively affecting patient safety and the quality of care (Arentsen et al, 2016; Cranford & Bates, 2015; Kahaleh, Danielson, Franson, Nuffer, & Umland, 2015). As a result, nursing educators are now required to include IPE content in their curricula (Poirier, & Wilhelm, 2013).…”
Section: Interprofessional Education and The Role Of Chaplaincy In Hementioning
confidence: 99%
“…Prior research has shown simulation as an effective pedagogical tool to deliver both IPE and EHR training [15,16]; further, clinicians who trained using EHR through simulation techniques significantly enhanced their safety and quality scores related to EHR usage [17]. Providing students an opportunity to utilize these skills in a structured IPE training environment may be critical to their later success when caring for patients [18,19,20].…”
Section: Methodsmentioning
confidence: 99%
“…Currently, few studies have compared the effects of standardised patient simulation or role-play on nurses’ and nursing students’ competence to communicate with other healthcare professionals [ 18 , 37 , 38 , 39 ]. Studies comparing role-play versus traditional strategies, such as lectures and class discussions [ 18 , 38 , 39 ], observed an improvement in students’ competence in terms of knowledge and skills.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing role-play versus traditional strategies, such as lectures and class discussions [ 18 , 38 , 39 ], observed an improvement in students’ competence in terms of knowledge and skills. On the other hand, studies applying standardised patient simulation [ 20 , 37 , 40 ] showed inconsistent results in relation to students’ self-efficacy and skills. However, to the best of our knowledge, the effects of these strategies (standardised patient simulation vs role-play) on nursing students’ competence in interprofessional communication in elderly care have not been compared.…”
Section: Introductionmentioning
confidence: 99%